Modification of 4-(4-chlorothiophen-2-yl)thiazol-2-amine derivatives for the treatment of analgesia and inflammation: synthesis and in vitro, in vivo, and in silico studies - Mahnashi, Mater H.; Rashid, Umer; Almasoudi, Hassan Hussain; Nahari, Mohammed H.; Ahmad, Imran; Binshaya, Abdulkarim S.; Abdulaziz, Osama; Alsuwat, Meshari A.; Jan, Muhammad Saeed; Sadiq, Abdul (Frontiers in Pharmacology, 2024)
Inflammation is a protective response to variety of infectious agents. To develop a new anti-inflammatory drug, herein, we have explored a pharmacologically important thiazole scaffold. In a multi-step synthetic approach, we were able to synthesize seven new thiazole derivatives (5a – 5g). Initially, we examined the in-vitro anti-inflammatory potentials of our compounds by using COX-1, COX-2 and 5-LOX enzymes assays. After in-vitro confirmations, the potential compounds were subjected to in-vivo analgesic and anti-inflammatory studies. The hot plate method was used for analgesia, while the carrageenan induced inflammation was also assayed. Overall, all of our compounds proved to be potent inhibitors of COX-2 exhibiting IC50 values in the range of 0.76 to 9.01 μM in comparison to the celecoxib (IC50 0.05 μM). Compound 5b, 5d and 5e were dominant and selective COX-2 inhibitors with lowest IC50 values and SI of 42, 112 and 124 respectively. Similarly, in COX-1 assay, our compounds were relatively less potent, but still encouraging. The standard aspirin exhibited IC50 value of 15.32 μM. In 5-LOX results, again compounds 5d and 5e were dominant with IC50 values of 23.08 and 38.46 μM respectively. The standard zileuton exhibited IC50 value of 11.00 μM. Based on the COX/LOX and SI potencies, the compounds 5d and 5e were subjected in-vivo analgesic and anti-inflammatory studies. The compounds 5d and 5e at concentrations of 5, 10 and 20 mg/kg bw were significant in animal models. Furthermore, we explored the potential role of the compounds 5d and 5e in various phlogistic agents. Similarly, both of the compounds 5d and 5e were also significantly potential in anti-nociceptive assay. The molecular docking interactions of these two compounds with the target proteins of COX and LOX further strengthened their potential use in COX/LOX pathway inhibitions.